Neural Damage in Experimental Trypanosoma brucei gambiense Infection: The Suprachiasmatic Nucleus - Tesoriero, Chiara; Xu, Yuan-Zhong; Mumba Ngoyi, Dieudonné; Bentivoglio, Marina (Frontiers in Neuroanatomy, 2018)
Trypanosoma brucei (T. b.) gambiense is the parasite subspecies responsible for most reported cases of human African trypanosomiasis (HAT) or sleeping sickness. This severe infection leads to characteristic disruption of the sleep-wake cycle, recalling attention on the circadian timing system. Most animal models of the disease have been hitherto based on infection of laboratory rodents with the T. b. brucei subspecies, which is not infectious to humans. In these animal models, functional, rather than structural, alterations of the master circadian pacemaker, the hypothalamic suprachiasmatic nucleus (SCN), have been reported. Information on the SCN after infection with the human pathogenic T. b. gambiense is instead lacking. The present study was aimed at the examination of the SCN after T. b. gambiense infection of a susceptible rodent, the multimammate mouse, Mastomys natalensis, compared with T. b. brucei infection of the same host species. The animals were examined at 4 and 8 weeks post-infection, when parasites (T. b. gambiense or T. b. brucei) were detected in the brain parenchyma, indicating that the disease was in the encephalitic stage. Neuron and astrocyte changes were examined with Nissl staining, immunophenotyping and quantitative analyses. Interestingly, significant neuronal loss (about 30% reduction) was documented in the SCN during the progression of T. b. gambiense infection. No significant neuronal density changes were found in the SCN of T. b. brucei-infected animals. Neuronal cell counts in the hippocampal dentate gyrus of T. b. gambiense-infected M. natalensis did not point out significant changes, indicating that no widespread neuron loss had occurred in the brain. Marked activation of astrocytes was detected in the SCN after both T. b. gambiense and T. b. brucei infections. Altogether the findings reveal that neurons of the biological clock are highly susceptible to the infection caused by human pathogenic African trypanosomes, which have the capacity to cause permanent partial damage of this structure.